A polarization-induced InN-based tunnel FET without physical doping. (22nd May 2019) - Mao, Wei; Peng, Ziling; Yang, Cui; Wang, Haiyong; Du, Ming; Wang, Xiaofei; Zheng, Xuefeng; Wang, Chong; Zhang, Jincheng; Hao, Yue
Abstract: A new design approach for TFETs without physical doping is provided and demonstrated based on the polarization effect for the first time in this paper. And a polarization-induced InN-based TFET (PI-InN-TFET) is proposed and investigated by two-dimensional numerical simulations. Compared with the conventional physical doping InN-based TFET (D-InN-TFET), the proposed device features the formation of P-type source and N-type drain induced by the polarization effect near the InN-based heterojunctions without the need for any physical doping, which makes it possible for the PI-InN-TFET to avoid the random dopant fluctuation (RDF) and the problems related to the high thermal annealing techniques. Simulation results exhibit that the performance of the PI-InN-TFET is better than that of the optimized D-InN-TFET. Besides, the proposed PI-InN-TFET could be realized by the mature fabrication processing of the field-plated GaN-based HEMTs and could be further improved by introducing other techniques such as L-shaped TFET, T-shaped TFET.